Redox-Hopping-Based Charge Transport Mediated by Ru(II)-Polypyridyl Species Immobilized in a Mesoporous Metal-Organic Framework - Duan, Jiaxin; Goswami, Subhadip; Hupp, Joseph T. (Frontiers in Chemical Engineering, 2022)
Electronic charge transport through crystalline metal-organic frameworks (MOFs) can be accomplished by site-to-site electron (or hole) hopping, provided that redox-active sites, such as easily reducible or oxidizable MOF linkers, are present. If the framework itself is redox-inert, solvent-assisted ligand incorporation of redox-active moieties can serve to enable hopping-based charge transport. Here we have studied the redox hopping process within Ru-bpy@NU-1008, where Ru-bpy is a carboxylate-functionalized derivative, i.e., a node-ligating derivative, of the well-known chromophore Ru(2,2′-bipyridine)32+, and NU-1008 is a redox-inert MOF featuring hierarchical porosity and csq topology. Chronoamperometry experiments with electrode-supported thin films of Ru-bpy@NU-1008 show that charge transport is feasible through portions of the MOF, with other portions being inaccessible. Possible confounding features are the undersized c-pores that cross-connect 1D mesoporous channels, as ingress and egress of charge-compensating anions is believed to accompany the net oxidation of Ru(II) to Ru(III) and the reduction of Ru(III) to Ru(II). Phenomenologically, transport through the electroactive portion of the films is diffusion-like, with the magnitude of the apparent diffusion coefficient being 6 × 10−12 cm2/s.